Emergent Specters and Disruptive Play in the Production of Disc Golf. Issue 3 (3rd July 2022) - Colucci, Alex R.
ABSTRACT: Disc golf is experiencing immense recent growth that, in 2020, noticeably outpaced the steady growth seen in the sport over the past decade. This spirited movement has vaulted disc golf into the position of a suddenly and perhaps unexpectedly emerging sport. "Growth" has become a central paradigm around which the sport (its institutions and participants) concentrates. Alongside this emergence, social and political issues emerge, unexpectedly for some, from the sport's (recent) past that serve to challenge its present trajectory. To examine these emergences, I develop Derrida's associated concepts of hauntology, absence/presence, and the trace to draw out and play with connections between the sport's emergence issues. Revolving around "growth" as a central paradigm, production, excess, access, diversity, inclusion, toxicity, and sustainability all appear as related issues in the sport's emergent present. Beginning with empirically based vignettes, I question the present social material condition of disc golf. This questioning, and emerging understanding, proceeds by drawing connections between the present condition of social relations in the sport and social and political theory. Here, I draw on an array of post-structural and political-economic theory during my analysis to carry through the vocabulary established by a hauntological framework and a sense of play. The resulting deconstruction provides both a playful vocabulary and conceptual apparatus for analyzing disc golf's emergence and the status of other emerging sports. This process, in turn, demonstrates the transformative potential of embracing the decentering, disruptive potential inherent to 'play' in the double sense. The "play" of writing (with language) and the "play" of direct action that promotes difference to challenge fixed positions that are central to producing cultural phenomena, such as disc golf.